Scientific Study: Enhancing Baby's Body Immunity Through the Javanese Tahnik Tradition - Nurutstsany, Elfrida; Fujiyanti, Hersy (Proceeding International Conference on Science and Engineering, 2019)
Existence of Javanese culture is still inherent in modern times with beliefs that cannot be abandoned. Tradition nyetaki is an expression of gratitude to God about the birth of a child. Based on the view of Islam, it is called tahnik, which is to chew dates until smooth and then put into the baby's mouth and rub it into the palate so that there are some dates that are swallowed. In addi tion to dates, foods that are commonly used are sweet foods. Tahnik is done by people who are considered experts in religious science or have a high spiritual spirit. In the basics saliva and mouth store various kinds of bacteria. The phenomenon that occurs due to the tradition of tahnik is to strengthen the baby's immunity. The research method is descriptive explorative qualitative. Data and sources are obtained through observation to the community and literacy studies from various valid reference sources. This study examines the local wisdom that is trusted by the people of Java about Islamic immunization. Cultural know-how involves dental peristalsis, oral amylase enzymes, and bacteria in the mouth. Positive bacteria in the tahnik process will move to the baby's stomach so as to stimulate natural immunity. The bacteria contained in the mouth will make the natural immune system, so the body is resistant to these bacteria. The mouth contains an amylase enzyme that can break down glucose. Baby's glucose needs are less than 20 mg/100 mL - 30 mg/100 mL of blood so that they are susceptible to contracting the disease. So, dates or sweet foods that contain carbohydrates break down into simple molecules and speed up the digestive process. The spiritual value of the power of prayer and public trust strengthens the baby's immune system.